PEMETAAN PENELITIAN KEMAMPUAN AWAL LITERASI DIGITAL PADA PENDIDIKAN DASAR: TINJAUAN BIBLIOMETRIK - Nurcahyanti, Mei; Fitriana, Novita; Faisal Hidayat, Akhmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the initial digital literacy skills of elementary school students through a bibliometric review approach. Digital literacy is an essential competency of the 21st century that encompasses not only the technical skills of using technology but also the skills of critical thinking, information evaluation, communication, collaboration, and awareness of digital security. The research method used was a Systematic Literature Review (SLR) with bibliometric analysis referring to the PRISMA guidelines. Data were obtained from 11 articles from 2021–2026, then selected to four articles that met the inclusion criteria and analyzed using VOSviewer software. The results show that the trend of digital literacy publications in elementary education has increased significantly, and is dominated by the theme of digital literacy integration in learning. Substantively, the initial digital literacy skills of elementary school students are in the fairly good category, especially in the aspects of critical thinking and the ability to find information, but are still low in the aspects of digital security, collaboration, and creativity. This study also found that teacher competence, infrastructure support, and parental guidance are important factors in the development of students' digital literacy. Furthermore, digital literacy has two main dimensions: as an educational opportunity and as a potential risk if not managed properly. Therefore, developing digital literacy from an early age requires a comprehensive and sustainable approach to fostering a generation that is critical, creative, and responsible in utilizing digital technology.